PENILAIAN KINERJA UNTUK PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN DI KOPERASI MODERN TRIKORA - Sudarmansyah, Asep (Journal Tafkirul Iqtishodiyyah, 2024)
Employee work productivity, as previously explained, can be measured through the results of their work performance assessment. This assessment not only provides an overview of performance, but can also encourage high levels of satisfaction among employees. The results of the analysis show a value of r = 0.9597, which shows that there is a strong and positive relationship between job performance assessments and work productivity. Apart from that, calculations also reveal that the contribution of performance appraisal to employee productivity reaches 92%, while the remaining 8% is influenced by other factors outside of the appraisal. The implementation of the work performance assessment at the Trikora Modern Cooperative aims to evaluate whether the work standards and targets set have been achieved. This also functions as input in decision making in the field of personnel as well as in various other aspects of the Trikora Modern Cooperative